POLITIK HUKUM PENGAWASAN HAKIM KONSTITUSI - Muhtadi, Muhtadi (Lampung University, 2015)
In order to preserve and uphold the honor, dignity, and the behavior of the judge is required to supervise the attitude constitutional judge to fit the code of ethics, so that each judges ruling will be implemented in order to enforce the law and justice based on Pancasila and the Constitution 1945 as a permanent legal political for supervision of the constitutional judges. Whereas legal politics incidental that becomes choice among others: a) Behavior of Constitutional Judges are overseen by the Board of Ethics established by the Constitutional Court, and for the reported judges or suspected violations of ethic codes of Constitutional Judges formed by Honorary Council of the Constitutional Judges whose creation was proposed by Ethics Council, with the task of implementing and serves as ethic judicial; and b) there is no judicial supervision against Constitutional Courts decision as well as supervision of a court decision which was in the Supreme Court through the mechanism of legal remedies (ordinary and extraordinary).Â Keywords: Supervision, Behavior, Constitutional Judges